Low-Income Residents' Perceptions of Medication Availability. Issue 2 (3rd April 2019) - Johnson, Rolanda; Cook, Tom
ABSTRACT: Access to medications is a critical determinant of health which often mediates the effects of diseases and leads to healthier lifestyles. With limited access to pharmacies, neighborhoods become pharmacy deserts. The purpose of this study was to explore the medication needs and perceptions of low-income community residents. A purposive sample of 40 low-income community residents participated in focus groups. Content analysis revealed four themes: transitioning to the present, stereotyping, feelings of disconnectedness, and ideal pharmacy. These findings reiterate the difficulties of living in pharmacy deserts, and decrease the gaps of limited qualitative research in this area.